ANALISIS PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN SIKAP TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Pos Ketan Legenda 1967 Kota Semarang) - Khoiruddin, Muhammad Afif; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2017)
This study aims to analyze the effect of product quality, price perceptions and attitude toward purchase decision. The object of this research is Pos Ketan Legenda 1967 Semarang City. Variables used in this study are product quality, price perceptions and attitudes as independent variables and purchasing decisions as the dependent variable. The sample used in this study as many as 151 respondents are the consumers who have bought the Pos Ketan Legenda 1967 Semarang City.The method used is Purposive Sampling by distributing questionnaires to the respondents who are specifically addressed to Pos Ketan Legenda 1967 of Semarang City. Collected datas were analysed with IBM SPSS 22 for windows using some methods such as validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, ANOVA, R Square, and T test.The results showed that product quality positively influence to purchase decision, price perception have positive effect to purchasing decision and attitude have positive effect to purchasing decision.